Metaverse as challenge to homo religionis: Diachronic thinking in theory formation for pastoral caregiving to netizens - Louw, D. J. (Acta theologica, 2024)
Metaverse brings about the reshaping of the playful human being (homo ludens) into the digitalised human being (homo digitalis). Transcendence (homo transcendentalis) has become digitalised by the power of technologised options (optimalisation of our being human) and fictive forms of sublimations (avatars). Due to, inter alia, Facebook and Instagram, a spirituality of diachronic networking and digital immediacy, set in: I start to exist through and via (Greek: dia) the digitalised other. Thus, the following research question: How could metaverse thinking contribute to a multidimensional reinterpretation of religious spirituality?